A finite-volume method for full-scale simulations of coaxial borehole heat exchangers with different structural parameters, geological and operating conditions. (January 2022) - Jia, G.S.; Ma, Z.D.; Xia, Z.H.; Zhang, Y.P.; Xue, Y.Z.; Chai, J.C.; Jin, L.W.
Abstract: The coaxial borehole heat exchangers (BHEs) are commonly used for efficient heat exchange between the heat carrier (usually water) and geothermal energy. Driven by the demand for the performance evaluation of extremely large length-diameter ratio BHEs under various working conditions in the practical engineering, this article presents a high-efficiency finite-volume computational model using variable-length control volumes to study the thermal behaviors of coaxial BHEs. The solution method is validated using data collected from three wells of 47.2 m, 879.6 m and 2, 600.0 m depths. It is also used to guide the structural design and performance optimization of BHEs. The comparisons show that the present method can accurately predict the BHE performance with different structures, geological conditions and operating modes. With more reasonable thermal conductivity values, an approximate 100 kW deviation between the predicted and test heat exchange rates was avoided, and RMSE of the outlet temperature was improved from 4.09 to 0.82 for a 2, 600 m BHE. The application of the proposed method in engineering projects indicates that setting the periodic operation interval of geothermal wells, according to the building types and heating demand, is an important factor to optimize the utilization of geothermal energy for space heating. Highlights: An FVM computational model is developed to evaluate the performance of coaxial BHEs. The variations of geothermal parameters are integrated in the full-scale model. Thermal properties are assigned to different geological layers for better prediction. The method predicts both continuous and intermittent operating modes well. The method is applicable for BHE projects with extremely large length-diameter ratio.